2016
DOI: 10.1111/are.13034
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic and antioxidant effects ofMyrcia sylvatica(G. Mey.)DC. andCurcuma longaL. essential oils on tambaqui (Colossoma macropomum)

Abstract: Anaesthetic substances are necessary to reduce fish stress during aquaculture activities. The objectives of this study were: (i) to determine the efficacy of essential oils (EOs) of Myrcia sylvatica (EOMS) and Curcuma longa (EOCL) as anaesthetics for Colossoma macropomum and (ii) to evaluate the effects of rapid anaesthesia and long-term sedation (6 h) with these oils. Therefore, the main primary stress indicator (cortisol) and secondary factors (biochemical indices, hepatic metabolism, oxidative biomarkers) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 71 publications
(123 reference statements)
3
43
1
5
Order By: Relevance
“…Similar results were found in R. quelen and Paralichthys olivaceus fed with diets containing rutin (Pês, Saccol, Ourique, Londero, Gressler, Finamor et al., ) and quercetin (Shin, Yoo, Min, Lee, & Choi, ), respectively, both compounds considered as important antioxidants. Regarding the effects of EOs, several studies have shown that these substances act as anaesthetics and prevent an increase in plasma cortisol levels in different fish species, supposedly blocking sensorial transmission to the hypothalamus, as well as the subsequent triggering of the hormonal cascade (Gressler et al., ; Iversen, Finstad, McKinley, & Eliassen, ; Saccol, Londero et al., ; Saccol, Toni et al., ). However, the exact mechanism underlying the effect of EOs on cortisol secretion remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar results were found in R. quelen and Paralichthys olivaceus fed with diets containing rutin (Pês, Saccol, Ourique, Londero, Gressler, Finamor et al., ) and quercetin (Shin, Yoo, Min, Lee, & Choi, ), respectively, both compounds considered as important antioxidants. Regarding the effects of EOs, several studies have shown that these substances act as anaesthetics and prevent an increase in plasma cortisol levels in different fish species, supposedly blocking sensorial transmission to the hypothalamus, as well as the subsequent triggering of the hormonal cascade (Gressler et al., ; Iversen, Finstad, McKinley, & Eliassen, ; Saccol, Londero et al., ; Saccol, Toni et al., ). However, the exact mechanism underlying the effect of EOs on cortisol secretion remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those found in previous studies on this plant. In the study of Saccol, Toni et al (2017), the major components of the EOMS were β-selinene (9.96%), cadalene (9.36%), α-calacorene (9.17%) and Z-calamene (8.17%), whereas Silva et al (2016) they found these and others components at higher percentages, such as 1-epi-cubenol (9.9%), cadalene (7.2%), β-selinene (7.0%),…”
Section: Eoms Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of plant essential oils as dietary supplements in aquaculture was recently reviewed (Sutili et al 2017) but to our knowledge, only two studies have considered the effects of plant extracts on stress tolerance during transportation through administration as a dietary supplement. Turmeric (Curcuma longa, Linnaeus 1758) has a variety of documented medicinal properties (anti-inflammatory, Ara ujo & Leon 2001;immunostimulant, Chattopadhyay et al 2004;antioxidant, Luthra et al 2001;Saccol et al 2016;anaesthetic, Saccol et al 2016;antimicrobial, Luthra et al 2001;antiparasitic, Ara ujo & Leon 2001). Supplementing the diet of juvenile yellow tail tetra (Astyanax aff.…”
Section: Introductionmentioning
confidence: 99%